Expert knowledge in judicial decisions: Colombian environmental cases - Gaitán Reyes, Julián Andrés (DIXI, 2022)
Objective: To analyze the valuation criteria used by judges when using expert knowledge in certain environmental protection cases. Methodology: This study is designed with qualitative considerations about the valuation criteria used by judges to validate expert knowledge in Colombian environmental law court rulings. A specific unit of a population universe was analyzed, in order to construct categories of analysis from documentary sources obtained from the Colombian High Courts’ consultation system, under a non-probabilistic sampling. Results: The ways in which judges used expert knowledge were identified and the criteria for weighting the use of expert knowledge in the judicial decisions under study were established. Conclusions: The evaluation criteria used by judges to validate expert knowledge in judicial decisions on Colombian environmental law were: suitability of the experts and reliability of the expert information, due to the fact that they come from state sources that are accepted by the scientific community.